The Meaning of Gesture in Social Cultural Context - Najamuddin A (Universitas Islam Negeri Mataram, 2019)
This articlces intents to describe the meaning of gestures in sosialcultural context, especially for students in language learning and generally forlanguage user which have different cultural background and to encouragean appreciation of cultural diversity and the process of interculturalcommunication.Students and people still find difficulties to learn, tounderstand the gestures and leaves them confused about what the meaningof gestures apply in context of situation and culture. This confusion is due tocountless rules governing proper of gestures.Based on the brief explanationabove, speakers of languages in certain cultures that use “gestures” canchange the meaning or the meaning conveyed. Thus, the problem is likewhat gesture used by speakers of the language so that what is deliveredis not responded well, of course based on different cultural backgrounds.Gestures serve different purposes in language. Function gestures makesymbol of language has meaningful. Content of gestures are the symbolsthat communicate meaning in contexts. Clearly, people must know kinds ofgestures to understand what they act.